Severe traumatic brain injury: outcome in patients with diffuse brain injury without surgical lesion managed in Hospital Sultanah Aminah, Johor Bahru an observational study - Liew Boon, Seng (2009)
Severe traumatic brain injury has been one of the major causes of death in Malaysia. There has been limited numbers of intensive care facilities to cater for the escalating numbers of severe traumatic brain injury patients. Due to the limitation, not all the patients in this group been managed strictly according to the recommendations given by the Brain Trauma Foundation, especially those who did not warrant any neurosurgical intervention such as a craniotomy.The aim of this research was to compare the outcome of the severe traumatic brain injury with diffuse brain injury without surgical lesion treated with different treatment modalities, namely ICP-CPP-targeted, ventilation and intubation groups. This research also aims to assess the usefulness of routine serial head computed tomography (CT scan) in severe traumatic brain injury patients with diffuse brain injury without surgical lesion. It is also aims to identify factors influencing the outcome of severe brain injury patients with diffuse brain injury without surgical lesion and to determine the hazards risk of severe traumatic brain injury patients with diffuse brain injury without surgical lesion. This was a prospective observational study of severe traumatic brain injury patients admitted with diffuse brain injury without surgical lesion as defined by Marshall's Classification for Diffuse Injury, to Neurosurgical Intensive Care Unit (NICU), Hospital Sultanah Aminah, Johor Bahru. The study was conducted between 1st December 2006 and 31th May 2008 with a total of 72 patients included in the study. The patients' recruitment period was from 151 December 2006 to 30th November 2007. The follow-up was done at the third month and sixth month from the date of discharge of the recruited patients, which ended on 31th May 2008. All patients were with severe traumatic brain injury patients of both sexes, with the admission GCS of eight or below and sustained blunt head injury without surgical or mass lesion and admitted via direct admission or transferred from other hospital within 24 hours post trauma. Surgical or mass lesion defined as any high or mixed-density lesion of more than 25 cc, as defined by Marshall's CT Classification. Patients with polytrauma which caused unstable hemodynamic status, requmng immediate non head surgical intervention and post operative ventilation support, severe underlying medical disorders such as major organ failure, endocrinological or hematological disorder, suspected drug or alcohol intoxication, mentally subnormal, or history of chronic epilepsy before the event of head trauma, or who on arrival had unilateral or bilateral fixed and dilated pupils believed to be due to ongoing herniation, clinically showing absence of brain stem reflexes, with no improvement after resuscitation or failed resuscitation upon admission and patients who had a known history of hemiparesis, or had any other condition that lowered the patient's functional status score were excluded in the study. Data entry and analysis was done using Statistical Package for Social Sciences (SPSS) version 12. 0.1 Means and standard deviations were calculated for continuous variables ' and frequency and percentages for categorical variables. Pearson Chi-square Test was used for categorical data between two groups (good and poor outcome). Pearson Chisquare values were determined, however if the expected frequency of less than five were more than twenty percent of the cells, Fisher's Exact Test was applied. Chisquare was applied to assess association between binary dependent variable and three treatment variables. One-Way ANOVA was applied for numerical variables of three treatment variables after normality checking when the assumptions were met. Median and interquartile range were calculated for numerical variable if it was not normally distributed and Kruskal Wallis Test was applied. Multiple Mann-Whitney Tests were performed and interpreted if the p value was significant. The significant value was set at p value less than 0.05. The prognostic factors of diffuse brain injury without surgical lesion among severe traumatic brain injury patients were determined using Cox Proportional Hazards Regression Model. For Multiple Cox Proportional Hazards Regression Model, forward stepwise was applied. Log-minus-log plot, hazards function plot and partial residuals were applied to check the model assumption. Seventy two patients with severe traumatic brain injury with diffuse brain injury without surgical lesion treated in NICU, Hospital Sultanah Aminah, Johor Bahru between 1st December 2006 and 30th November 2007 were studied. The age of patients were ranging from eight to 64.8 years old, with median age at 34.1 years old, mean age of 34.2 years old and standard deviation of 14.7 years old. Majority of patients were male, with 61 patients (84. 7%) and remaining 11 patients were female. From a total of 72 patients admitted for diffuse brain injuries, without any surgical lesion, 41 (56.2%) were just treated with intubation for airway protection, and given oxygen via oxyvent device with continuous oxygen saturation monitoring. A total number of 16 patients were treated with ventilation support due to various reasons, which include cerebral resuscitation without ICP-CPP guided management. There were only 15 (20.8%) patients who were treated with standard ICP-CPP guided cerebral resuscitation. Eleven patients died during hospitalization (15.3%). Out of remaining 61 patients, only 49 patients (80.3%) were follow-up during first three months (with three deaths) and 45 out of 58 patients (77.6%) were follow-up during subsequent three months (with no death detected). On first third month follow-up, seven (15.2%) were still severely disabled, with moderate disability reported in four patients and 29 (63%) patients with good recovery. On the next sixth month follow-up, there were left with only one patient with severe disability, while the rest of 44 (97.8%) patients were improved with either moderate or good recovery. Outcome was worse in the ICP-CPP targeted group with median(IQR) GOS score of 2.00(2) compared to intubation group with median (IQR) of 4.00(1) and 3.00(1) in ventilation group upon discharge. This finding was statistically significant for a worse outcome in ICP-CPP targeted group than intubation group. (p=0.001). This difference was also seen during frrst three months follow-up but it was between intubation group and ventilation group (p=0.012) with lower median GOS in ventilation group. At sixth months follow-up, intubation group had a better median GOS compared with ICP-CPP targeted group and ventilation group, with statistically significant p value of <0.001 and p=0.004 respectively. Routine CT scans were done and our findings showed that 42 (80.8%) patients did not show any progression. None of patients where a repeat HCT showed progression without clinical deterioration was given any intervention. The analysis demonstrated that the following factors were statistically significant associated with outcome at six months follow up: Best motor response on admission (p=0.012); Glasgow Coma Score (GCS) on admission (p=0.007); Rapid eye movement {p=O.OOl) and Type of diffuse injury {p=0.009). There was statistically significant of the increase in the hazards of dying in ICP-CPP targeted management group compared to intubation group {p=0.008). In diffuse brain injury without surgical or significant mass lesion, the severity of the brain injury may not be as bad compared with those with associated surgical lesion such as intracerebral hemorrhage and acute subdural hemorrhage. This is concluded based on the finding of lower hospital mortality rate (15.3%) in this subgroup of patients with severe head injury compared to most studies which included those with surgical lesion, with mortality rate between 20.7% and 37.8%. This finding may be influenced by a high number of patients with diffuse injury type I and II, which were not associated with increased intracranial pressure compared to type III and IV. In term of recommendations for management of brain trauma, specific treatment plan may be needed for patients with diffuse brain injury without surgical lesion. The devastating outcome of patients treated with the best recommended plan shown in this study may alert us if we have done more than what is required. However, the poor outcome seen in this group of patients may be resulted from the primary brain injury itself, as most of them with more depressed level of consciousness on admission and with more severe diffuse brain injury seen in CT imaging. Based on the study, I would like to propose a more conservative management which may be suitable for a subgroup of patients with minimal CT findings of Diffuse Injury type I and II, with better admission GCS between six and eight, normal motor response and with strong evidence of rapid eye movement on admission. Otherwise they should be treated with the best available facilities as recommended by The Brain Trauma Foundation.